Role of proteomics in understanding prion infection. (December 2012) - Campisi, Edmondo; Cardone, Franco; Graziano, Silvia; Galeno, Roberta; Pocchiari, Maurizio
Transmissible spongiform encephalopathies or prion diseases are fatal neurodegenerative pathologies characterized by the autocatalytic misfolding and polymerization of a cellular glycoprotein (cellular prion protein [PrP C ]) that accumulates in the CNS and leads to neurodegeneration. The detailed mechanics of PrP C conversion to its pathological isoform (PrP TSE ) are unclear but one or more exogenous factors are likely involved in the process of PrP misfolding. In the last 20 years, proteomic investigations have identified several endogenous proteins that interact with PrP C, PrP TSE or both, which are possibly involved in the prion pathogenetic process. However, current approaches have not yet produced convincing conclusions on the biological value of such PrP interactors. Future advancements in the comprehension of the molecular pathogenesis of prion diseases, in experimental techniques and in data analysis procedures, together with a boost in more productive international collaborations, are therefore needed to improve the understanding on the role of PrP interactors. Finally, the advancement of 'omics' techniques in prion diseases will contribute to the development of novel diagnostic tests and effective drugs.